The role of ferritin in liver disease assessment - V. G. Radchenko; V. B. Grinevich; E. S. Ivanyuk; L. B. Lazebnik (Фармакоэкономика, 2023)
Background. Ferritin is an important integral and diagnostic marker of liver diseases. In 1/3 of patients with nonalcoholic fatty liver disease (NAFLD), manifestations of hyperferritinemia are revealed. Increased ferritin level indicates the severity of the disease course and affects the prognosis.Objective: to determine the prevalence and character of hyperferritinemia manifestations in NAFLD patients and to evaluate the effectiveness of its correction with human placenta hydrolysate.Material and methods. We examined 158 patients aged from 20 to 63 years (92 men and 66 women). There were no significant differences in age between men and women. The control group consisted of 20 practically healthy individuals. Molecular mechanisms of peptide components of human placenta hydrolysate (Laennec®) impact on pathophysiological processes of serum ferritin disorders, iron metabolism indicators, and inflammation manifestations were analyzed.Results. Nineteen peptides potentially important for regulation of iron homeostasis were identified in Laennec® composition. These peptides contribute to the elimination of iron metabolism disorders by regulating the levels of hepcidin (the main hormone of iron homeostasis), reducing ferritin synthesis, as well as exhibiting anti-inflammatory, and immunomodulatory effects. The efficacy of the drug monotherapy in patients with hyperferritinemia was shown.Conclusion. Laennec® was found to be one of the medicines contributing to the reduction of hyperferritinemia manifestations, iron metabolism disorders, and systemic inflammatory process in NAFLD.